Review Penerapan Smart City dalam Sistem Informasi Desa - Gunawan, Gunawan; Kurniawan, Yan; Andriani, Wresti (Publica Scientific Solution, 2022)
Introduction: The industrial era 4.0 and civil society 5.0 have changed the paradigm of culture, especially in rural communities thatnot only want innovation in sustainable rural development but in the form of administrative and non-administrative services carried outby the Village Government wanting excellent service. The community paradigm that wants everything to be on time and to fulfill the need for good service is the desire and hope of the community. So that a solution is needed from the Village Government, oneof which is the application of the intelligent village concept,which is based on Total Quality Service (TQS) and remains focused on service satisfaction for customers (village communities). Purpose: to analyze the review of the implementation of smart cities in village information systems. Methods: The method used is a qualitative research method with the research locus in several villages in the Pemalang Regency area. Results: The intelligent village concept has been appliedin several towns in the Pemalang Regency area,which is oriented to deliveringvillage information and assisting in providing services to the community. The results achieved are prettygood but require improvements in the applied management information system. Conclusion: The PemalangRegency Government utilizes rural sites/websites facilitated by PUSPINDES to develop the Pemalang area. Conduct village website management training. It usesICT for public information disclosure. Utilize ICT as a forum for village information and village promotion.